Geographical aspects of economic assessment of agricultural lands of Almaty agglomeration (Journal of Geography and Environmental Management, 2018)
The article considers the geographical aspects of the economic assessment of agricultural lands ofAlmaty agglomeration. Specificity of agricultural land use depends on natural and landscape features ofKazakhstan. A scientifically justified territorial organization of agricultural production should be implementedon the basis of accounting for both component-wise conditions and assessment criteria fornatural-landscape heterogeneity. Analyzing the diversity of types of natural landscapes on the territory ofthe Almaty agglomeration, it can be noted that the economic and geographical assessment of suburbanlands is impossible without taking into account the local approach. Each type, species, unit, district, areaof a specific landscape has its own specific characteristics, differently react to various anthropogenicimpacts, thereby differing in the economic value of the territory. As a result of the study, methodologicalrecommendations for improving the economic and geographical assessment of land resources in thesuburban areas of the Almaty agglomeration were developed.